Prevalence of Chronic Fatigue Syndrome and its association with quality of life and sleepy quality among young adults: a cross-sectional study - Yeo, Delphine Sze Qi (2024)
Background and Objective: Chronic fatigue syndrome (CFS), also called as myalgic encephalomyelitis (ME) is a exhausting clinical condition classified by continuous and unexplained fatigue after physical activity accompanied by a spectrum of symptoms linked to cognitive, immune, hormonal, and autonomic dysfunctions. Individuals affected by CFS are unable to perform their usual social, work, or recreational activities, and some of them may be restricted to home or bed. Their quality of life related to health is lower compared to individuals dealing with depression or those who have experienced a stroke condition. Therefore, this study aims to investigate the prevalence of chronic fatigue syndrome and its association with quality of life and sleep quality among young adults.